Intraperitoneal injection of the Porphyromonas gingivalis outer membrane vesicle (OMV) stimulated expressions of neuroinflammatory markers and histopathological changes in the brains of adult zebrafish - Adewoyin, Malik; Hamarsha, Ahmed; Akinsola, Rasaq; Teoh, Seong Lin; Azmai, Mohammad Noor Amal; Abu Bakar, Noraini; Nasruddin, Nurrul Shaqinah (Multidisciplinary Digital Publishing Institute, 2024)
Porphyromonas gingivalis is the major pathogenic bacteria found in the subgingival plaque of patients with periodontitis, which leads to neuroinflammation. The bacteria destroy periodontal tissue through virulence factors, which are retained in the bacteria’s outer membrane vesicles (OMV). This study aimed to determine the real-time effect of an intraperitoneal injection of P. gingivalis OMV on the production and expression of inflammatory markers and histopathological changes in adult zebrafishes’ central nervous systems (CNS). Following the LD50 (21 µg of OMV), the zebrafish were injected intraperitoneally with 18 µg of OMVs, and the control group were injected with normal saline at seven different time points. Brains of experimental zebrafish were dissected at desired time points for colorimetric assays, ELISA, and histology. This study discovered that nitric oxide and PGE2 were significantly increased at 45 min, while IL-1β and IL-6 were expressed at subsequent 12 h and 24 h time points, respectively. Histopathological changes such as blood coagulation, astrocytosis, edema, spongiosis, and necrosis were observed between the 6hour and 24 h time points. The two apoptotic enzymes, caspases 3 and 9, were not expressed at any point. In summary, the OMV-induced neuroinflammatory responses and histopathological changes in adult zebrafish were time-point dependent. This study will enrich our understanding of the mechanism of P. gingivalis OMVs in neuroinflammation in a zebrafish model, most especially the timing of the expression of inflammatory mediators in relation to observable changes in brain tissues.